The effects of pemafibrate and omega-3 fatty acid ethyl on apoB-48 in dyslipidemic patients treated with statin: A prospective, multicenter, open-label, randomized, parallel group trial in Japan (PROUD48 study) - Takeda, Yasutaka; Sakuma, Ichiro; Hiramitsu, Shinya; Okada, Mizuho; Ueda, Shinichiro; Sakurai, Masaru (Frontiers in Cardiovascular Medicine, 2023)
Background We compared the lowering effects of pemafibrate and omega-3 fatty acid ethyl on fasting apolipoprotein (apo) B-48 (apoB-48), a marker that reflects postprandial hypertriglyceridemia, which is one of the residual risks for atherosclerotic cardiovascular disease (ASCVD) with statin treatment. Methods This prospective, multicenter, open-label, randomized, parallel group trial was conducted at 4 medical institutions between April 2020 and May 2022. A total of 126 ambulatory patients with dyslipidemia receiving statin treatment for more than 4 weeks, aged 20–79 years with fasting triglyceride (TG) levels of ≥177 mg/dl were randomly assigned to 16-week pemafibrate 0.4 mg per day treatment group (PEMA, n = 63) or omega-3 fatty acid ethyl 4 g per day treatment group (OMEGA-3, n = 63). The primary endpoint was the percentage change in fasting apoB-48 from baseline to week 16. Results The percentage changes in fasting apoB-48 in PEMA and OMEGA-3 were −50.8% (interquartile range −62.9 to −30.3%) and −17.5% (−38.3 to 15.3%) (P < 0.001), respectively. As the secondary endpoints, the changes in fasting apoB-48 in PEMA and OMEGA-3 were −3.10 μg/ml (−5.63 to −1.87) and −0.90 μg/ml (−2.95 to 0.65) (P < 0.001), respectively. Greater decreases with significant differences in the percentage changes in TG, remnant lipoprotein cholesterol, apoC-III, fasting plasma glucose, alanine aminotransferase, gamma-glutamyl transpeptidase, and alkaline phosphatase were observed in PEMA, compared with OMEGA-3. Greater increases with significant differences in those in high-density lipoprotein (HDL) cholesterol, apoA-I, and apoA-II were observed in PEMA, compared with OMEGA-3. PEMA showed anti-atherosclerotic lipoprotein profiles in gel-permeation high-performance liquid chromatography analyses, compared with OMEGA-3. Although adverse events occurred in 9 of 63 (14.3%) patients in PEMA and 3 of 63 (4.8%) patients in OMEGA-3, no serious adverse events associated with drug were observed in either group. Conclusions This is the first randomized trial to compare the lowering effects of pemafibrate and omega-3 fatty acid ethyl on fasting apoB-48. We concluded that pemafibrate was superior to omega-3 fatty acid ethyl in lowering effect of fasting apoB-48. Pemafibrate is expected to reduce the residual risk for ASCVD with statin treatment. Clinical trial registration https://rctportal.niph.go.jp/en, identifier jRCTs071200011.